METHODS OF EVALUATION AND QUANTIFICATION OF DENTAL MOBILITY. SHORT REVIEW - Vieriu Raluca-Maria; Țănculescu Oana; Şufaru Irina Georgeta; Mârţu Silvia; Savin Carmen (Romanian Dental Association for Education, 2019)
The registration of dental mobility is an important step in the periodontal clinical examination. The most common methods used in practice are: clinical assessment method and instrumental mobilometry. Dental mobility can be recorded by objective or subjective methods, the latter frequently leading to errors in clinical evaluation and research.